Metallophthalocyanines as triplet sensitizers for highly efficient photon upconversion based on sensitized triplet–triplet annihilation. Issue 8 (19th July 2016) - Han, J. L.; You, J.; Yonemura, H.; Yamada, S.; Wang, S. R.; Li, X. G.
Abstract : Photon upconversion emission from rubrene in the 550–620 nm region was achieved using new soluble palladium and platinum phthalocyanine sensitizers with maximum PUC efficiency ∼5.6%, excited by a 633 nm laser with power <20 mW cm −2 . Abstract : Soluble palladium and platinum phthalocyanines with coumarin moieties were synthesized with Q bands in the red and near-IR regions, in which the molar extinction coefficients were up to 1.01 × 10 5 cm −1 mol −1 . These metallophthalocyanines were coupled with rubrene and applied in photon upconversion systems based on triplet–triplet annihilation. The highest upconversion efficiency of the palladium phthalocyanine was 5.6%, which is higher than that of the platinum phthalocyanine–rubrene system. The larger molar extinction coefficient resulted in high upconversion capability (>10 5 cm −1 mol −1 ) and low saturation incident power (<20 mW cm −2 ).